2017
DOI: 10.3847/2041-8213/834/2/l9
|View full text |Cite
|
Sign up to set email alerts
|

Convection Destroys the Core/Mantle Structure in Hybrid C/O/Ne White Dwarfs

Abstract: A hybrid C/O/Ne white dwarf (WD) -an unburned C/O core surrounded by an O/Ne/Na mantlecan be formed if the carbon flame is quenched in a super-AGB (SAGB) star or white dwarf merger remnant. We show that this segregated hybrid structure becomes unstable to rapid mixing within 2,000 years of the onset of WD cooling. Carbon burning includes a weak reaction that removes electrons, resulting in a lower electron-to-baryon ratio (Y e ) in the regions processed by carbon burning compared to the unburned C/O core, maki… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 30 publications
6
51
0
Order By: Relevance
“…In contrast, the WD model with thermohaline mixing shown in Figure 4 has already reached a similar level of homogenization after 1 Myr and has almost completely homogeneous 12 C and Y e profiles after only 11 Myr. This behavior is similar to what was found in Brooks et al (2017).…”
Section: Series Model Initial Mass Rotation Overshooting Wd Model Masssupporting
confidence: 90%
“…In contrast, the WD model with thermohaline mixing shown in Figure 4 has already reached a similar level of homogenization after 1 Myr and has almost completely homogeneous 12 C and Y e profiles after only 11 Myr. This behavior is similar to what was found in Brooks et al (2017).…”
Section: Series Model Initial Mass Rotation Overshooting Wd Model Masssupporting
confidence: 90%
“…If future work shows that these flames do quench before reaching the center, then these models would not evolve towards AIC. In Brooks et al (2017), we showed that such a 'hybrid' WD is in fact unstable to convection as it cools. However, in the accretion scenario considered in this paper, the relatively short timescale to grow to M Ch ( Myr) means that the WD would not be fully mixed at the time it nears M Ch .…”
Section: Structure At Aicmentioning
confidence: 99%
“…We start with a 1.1M WD that, due to convective boundary mixing, had a 0.4M cold C/O core beneath a hot O/Ne mantle. As in Brooks et al (2017), we then allowed for complete mixing over 10 Myr and then placed this WD in a 3 hr orbital period binary with a 1.5M helium star. When the WD reaches 1.25M via accretion and steady helium burning, a carbon flame in the hot C/O ashes ignites and propagates into the star, as shown in Figure 6.…”
Section: C/o Wd Accretors As Aic Progenitorsmentioning
confidence: 99%
“…1 We find that the convective regions grow and mix material on a timescale set by the selected cooling timescale in our simulations. Likewise, the mixing prescription assumed in the stellar evolution calculations of Brooks et al (2017) led to the mixing of the stellar model on its cooling time. where ∇ T and ∇ ad are the actual and adiabatic temperature gradients, g is the local gravitational acceleration, ρ and P are the density and total pressure, and χ T = ∂ ln P/∂ ln T and χ ρ = ∂ ln P/∂ ln ρ are the compressibilities.…”
Section: Cooling Hybrid Wdsmentioning
confidence: 99%
“…In Section 3 we outline the equations being solved in our numerical simulations and devise an idealized problem that captures the key features of the cooling hybrid WD. In Section 4 we compare the results of our simulations to models that adopt the approach taken by Brooks et al (2017). In Section 5 we summarize and conclude.…”
Section: Introductionmentioning
confidence: 99%